2021
DOI: 10.1177/17562872211022296
|View full text |Cite
|
Sign up to set email alerts
|

Medical and non-medical interventions for post-operative urinary retention prevention: network meta-analysis and risk–benefit analysis

Abstract: Aims: To assess the efficacy in lowering post-operative urinary retention, urinary tract infection and lower urinary tract symptoms and the incidence of adverse events among 12 interventions and to perform risk–benefit analysis. Methods: Previous randomized controlled trials were identified from MEDLINE, Scopus and CENTRAL database up to January 2020. The interventions of interest included early ambulation, fluid adjustment, neuromodulation, acupuncture, cholinergic drugs, benzodiazepine, antispasmodic agents,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…One of these studies (i.e. Sirisreetreerux et al., 2021 ), had all entries ‘yes’ except for 11 (‘Whether appropriate suggestions were made for the specific direction of further research?’). The literature was included after an overall independent valuation by two researchers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these studies (i.e. Sirisreetreerux et al., 2021 ), had all entries ‘yes’ except for 11 (‘Whether appropriate suggestions were made for the specific direction of further research?’). The literature was included after an overall independent valuation by two researchers.…”
Section: Resultsmentioning
confidence: 99%
“…The pharmacological intervention mainly involves improving the contraction of the detrusor muscle and reducing urethral resistance, which may have a preventive effect on postoperative bladder dysfunction. Recently, some system reviews (Aue‐Aungkul et al., 2021 ; Jackson et al., 2019 ; Sirisreetreerux et al., 2021 ) explored the usefulness and safety of pharmacological interventions such as antispasmodic agents, non‐steroidal anti‐inflammatory drugs suppository, alpha‐adrenergic antagonist (Ghuman et al., 2018 ), cholinergic drug and opioid antagonist agents in preventing urinary retention. Past research (Aue‐Aungkul et al., 2021 ) has indicated that bethanechol, a type of cholinergic preparation, may reduce the chance of bladder dysfunction by lowering the volume of post‐void residual assessed 1 month after the surgery and may show better urodynamic assessment results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior meta-analyses carried out by Sirisreetreerux et al 46 and Jackson et al 47 demonstrated neostigmine efficacy, a medication classified as either a parasympathomimetic or a reversible cholinesterase inhibitor, in the management and prevention of POUR. Nonetheless, it is imperative to subject these medications to RCTs with substantial sample sizes to determine their clinical efficacy and patient acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…According to Sirisreetreerux et al ,[ 71 ] early ambulation, acupuncture, opioid antagonist agents, alpha-adrenergic antagonists, and non-steroidal anti-inflammatory drugs (NSAIDs) significantly reduce the incidence of POUR with no difference in adverse events.…”
Section: Preventionmentioning
confidence: 99%